Giải bài tập 3 trang 37 Chuyên đề toán 10 cánh diều
Bài tập 3. Chứng minh:
$C_{n}^{0}3^{n}+C_{n}^{1}3^{n-1}+...+C_{n}^{k}3^{n-k}+...+C_{n}^{n-1}3+C_{n}^{n}$
$=C_{n}^{0}+C_{n}^{1}3+...+C_{n}^{k}3^{k}+...+C_{n}^{n-1}3^{n-1}+C_{n}^{n}3^{n}$
với $0\leq k\leq n;k,n\in N$*
$C_{n}^{0}3^{n}+C_{n}^{1}3^{n-1}+...+C_{n}^{k}3^{n-k}+...+C_{n}^{n-1}3+C_{n}^{n}$
=$C_{n}^{0}3^{n}+C_{n}^{1}3^{n-1}\times 1^{1}+...+C_{n}^{k}3^{n-k}\times 1^{k}+...+C_{n}^{n-1}3\times 1^{n-1}+C_{n}^{n}\times 1^{n}$
$=(3+1)^{n}=4^{n}$
$C_{n}^{0}+C_{n}^{1}3+...+C_{n}^{k}3^{k}+...+C_{n}^{n-1}3^{n-1}+C_{n}^{n}3^{n}$
$=C_{n}^{0}\times 1^{n}+C_{n}^{1}\times 1^{n-1}3+...+C_{n}^{k}\times 1^{n-k}3^{k}+...+C_{n}^{n-1}\times 1^{n-1}3^{n-1}+C_{n}^{n}3^{n}$
$=(1+3)^{n}=4^{n}$
Vậy $C_{n}^{0}3^{n}+C_{n}^{1}3^{n-1}+...+C_{n}^{k}3^{n-k}+...+C_{n}^{n-1}3+C_{n}^{n}$
$=C_{n}^{0}+C_{n}^{1}3+...+C_{n}^{k}3^{k}+...+C_{n}^{n-1}3^{n-1}+C_{n}^{n}3^{n}$
Bình luận